Modified Gravity Model fQ,T and Wormhole Solution - S. Davood Sadatian; S. Mohamad Reza Hosseini (Advances in High Energy Physics, 2024)
We investigate wormhole solutions using the modified gravity model fQ,T with viscosity and aim to find a solution for the existence of wormholes mathematically without violating the energy conditions. We show that there is no need to define a wormhole from exotic matter and analyze the equations with numerical analysis to establish weak energy conditions. In the numerical analysis, we found that the appropriate values of the parameters can maintain the weak energy conditions without the need for exotic matter. Adjusting the parameters of the model can increase or decrease the rate of positive energy density or radial and tangential pressures. According to the numerical analysis conducted in this paper, the weak energy conditions are established in the whole space if α<0 and 12.56<β<25.12 or α>0 and β>25.12. The analysis also showed that the supporting matter of the wormhole is near normal matter, indicating that the generalized fQ,T model with viscosity has an acceptable parameter space to describe a wormhole without the need for exotic matter.